Kajian Kinerja Industri Kecil dan Desa Kerajinan dengan Metode Balance Score Card (BSC) dan Analytical Hierarchy Process (AHP) (Studi Kasus di Beberapa Sentra Industri Kecil di Kabupaten Sidoarjo, Pasuruan, Mojokerto dan Gresik) - Mochamad Tutuk Safirin (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The small industry and handycraft villages is the one of important thing on the economical structure, because of capability absorbing the human resources and exploiting the huge potential natural resources in Indonesia. The large amount of the small industry, but on the balance with the high performance. Thus, the development of the industry is low and get the difficulty competing toward the advance industry and imported product. The Metod which is used are Balanced Scorecard (BSC), and Analytical Hierarchy Process (AHP. The Balanced Scorecard was used to measure business/industry performance with 4 perspectives, i. e.: financial perspective, market. Perspective, internal business process perspective and study and development process perspective. The Analytical Hierarchy Process (AHP) method was used to measuring the weighted of the every perspective and every critical success factor. The result of the research indicate that the small industrial performance averages amount of 2.06 (medium category), The critical success factor influence much enough the low of the small industry performances are : ROI, TATO, MAPE and ROE. The map of the small industry and handycraft villages, based on the performance as followes: 23% small industry are on the low category, 62 % small industry are on the medium category, and only 15% industry are on the advance category.Keywords: Balanced Scorecard, Critical Succes Factors, Analytical Hierarchy Process (AHP)